Pengembangan Media Augmented Reality Bangun Ruang (ARBA) untuk Meningkatkan Literasi Matematis Siswa Kelas V Sekolah Dasar - Hartami, Hartami; Maarif, Samsul (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2025)
This study aims to develop a learning medium based on Augmented Reality Bangun Ruang (ARBA) and to examine its effectiveness in enhancing the mathematical literacy of elementary school students. The research is grounded in the low level of students’ mathematical literacy and the need for innovative, interactive learning media that align with the characteristics of digital-native learners. The research employed a Research and Development (R&D) approach using the 4D development model (Define, Design, Develop, Disseminate), involving 18 fifth-grade students from a public elementary school in Jakarta, selected through purposive sampling. Data collection instruments included expert validation, practicality questionnaires, and pretest-posttest assessments. The media expert validation showed a feasibility score of 91.66%, while the subject matter expert validation scored 87.50%, both classified as highly feasible. The practicality test also indicated that students very well received the ARBA media. Data analysis using paired t-tests and Normalized Gain (N-Gain) revealed a significant improvement in learning outcomes, with an N-Gain score of 0,9032 (high category) and a gain percentage of 90,3176% (highly effective category). These results demonstrate that the ARBA media is effective in improving students’ understanding of geometric solids and their mathematical literacy skills. The 3D visualizations and interactivity offered by ARBA help reduce the abstractness of the material while increasing student engagement and interest in learning. Therefore, ARBA can be recommended as an innovative solution for literacy-oriented mathematics instruction, especially for geometry topics at the elementary school level.